Signal Transmission of Biological Reaction-Diffusion System by Using Synchronization - Zhou, Lingli; Shen, Jianwei (Frontiers in Computational Neuroscience, 2017)
Molecular signal transmission in cell is very crucial for information exchange. How to understand its transmission mechanism has attracted many researchers. In this paper, we prove that signal transmission problem between cancer cell and drug molecules can be achieved by synchronous control. To achieve our purpose, we derive the Fokker-Plank equation by using the Langevin equation and theory of random walk, this is model which can express the concentration change of drug molecules. Second, according to the biological character which vesicles in cell can be combined with cell membrane to release the cargo which plays a role of signal transmission. Third, we propose the the view of synchronous control which the process of vesicle docking with their target membrane is a synchronization process, so we can achieve the precise treatment of disease by using synchronous control. We believe this synchronous control mechanism is reasonable and two examples are given to illustrate the correctness of our results obtained in this paper